Comparison of Indonesian Private Lecturer Wage Systems With The Netherlands From Jhon Rawls' Legal Perspective - Abas, Muhammad (SASI, 2025)
Introduction: Higher education plays an important role in the development of a country, with lecturers as one of its main pillars. The quality of higher education is highly dependent on the performance and dedication of lecturers, which in turn is influenced by the wage system applied.Purposes of the Research: To evaluate the suitability of private lecturer wage systems in Indonesia and the Netherlands with John Rawls' concept of justice. To analyze various components of the wage system, including the structure of basic salary and allowances, a salary increase system based on achievement and length of service, and career development opportunities available to lecturers.Methods of the Research: Qualitative method with a descriptive-comparative approach to provide an in-depth picture and compare them within the framework of John Rawls' theory of justice. The research data sources include primary data obtained through in-depth interviews with relevant officials at the Ministry of Education, representatives of private university associations, and private lecturers in both countries, as well as secondary data from policy documents, laws and regulations, statistical reports, and academic literature.Results Main Findings of the Research: The Netherlands system is also supported by more comprehensive social security and effective negotiation, so that the wage gap between institutions is smaller. Indonesia still needs to make significant improvements in the implementation of regulations, wage standardization, and increasing social protection to achieve a level of fairness and welfare equivalent to the Dutch system. These differences reflect not only variations in university policies, but also the broader economic and social context in both countries.